Vitamin D Supplementation and its Effect on Modified Rankin Scale and National Institutes of Health Stroke Scale Outcomes in Acute Ischemic Stroke: A Systematic Review and Meta-Analysis - Andra Danika; Paulus Alexander Supit; Maria Stefanny Setiawan (The International Journal of Medical Science and Health Research, 2025)
Introduction: The role of vitamin D in functional recovery after acute ischemic stroke remains unclear due to inconsistent evidence. This systematic review and meta-analysis aim to evaluate the effect of vitamin D supplementation on functional and neurological recovery, as measured by the modified Rankin Scale (mRS) and the National Institutes of Health Stroke Scale (NIHSS), in adult patients with acute ischemic stroke. Methods: Following PRISMA 2020 guidelines, a systematic search was conducted in PubMed, Google Scholar, and Semantic Scholar for randomized controlled trials and meta-analyses since 2015. Eligible studies included adult ischemic stroke patients receiving vitamin D supplementation with reported mRS or NIHSS outcomes. Data were synthesized, and random-effects meta-analyses calculated pooled hazard ratios (HRs). Results: Vitamin D supplementation was associated with significant improvements in mRS (HR 1.32) and NIHSS (HR 1.30). However, substantial heterogeneity was observed (mRS I² = 78.4%; NIHSS I² = 77%). Variability largely stemmed from differences in supplementation regimens (single high-dose injection vs. daily oral) and the baseline vitamin D status of participants. Discussion: Findings suggest vitamin D may enhance post-stroke recovery, though the benefit is not consistent across populations. Improvements were most evident among patients with pre-existing deficiency, indicating supplementation may be particularly effective as corrective therapy. Variation in dosage and timing complicates the formulation of a single treatment recommendation Conclusion: Vitamin D supplementation is associated with a statistically significant improvement in functional and neurological outcomes for patients with acute ischemic stroke, as measured by the mRS and the NIHSS. The pooled data suggests a beneficial role for vitamin D in post-stroke recovery